Voigt profile introduces optical depth dependent systematic errors – Detected in high resolution laboratory spectra of water. (February 2016) - Birk, Manfred; Wagner, Georg
Abstract: The Voigt profile commonly used in radiative transfer modeling of Earth׳s and planets׳ atmospheres for remote sensing/climate modeling produces systematic errors so far not accounted for. Saturated lines are systematically too narrow when calculated from pressure broadening parameters based on the analysis of laboratory data with the Voigt profile. This is caused by line narrowing effects leading to systematically too small fitted broadening parameters when applying the Voigt profile. These effective values are still valid to model non-saturated lines with sufficient accuracy. Saturated lines dominated by the wings of the line profile are sufficiently accurately modeled with a Voigt profile with the correct broadening parameters and are thus systematically too narrow when calculated with the effective values. The systematic error was quantified by mid infrared laboratory spectroscopy of the water ν2 fundamental. Correct Voigt profile based pressure broadening parameters for saturated lines were 3–4% larger than the effective ones in the spectroscopic database. Impacts on remote sensing and climate modeling are expected. Combination of saturated and non-saturated lines in the spectroscopic analysis will quantify line narrowing with unprecedented precision. Highlights: Systematic errors of Voigt line profile for saturated lines discovered. Combination of saturated and non-saturated lines good source for narrowing parameters. Findings have high relevance for remote sensing. Saturated lines can be modeled with high accuracy by Lorentz profile.